2020
DOI: 10.20965/jaciii.2020.p0829
|View full text |Cite
|
Sign up to set email alerts
|

FR-MTL: Traffic Flow Prediction Using Fused Ridge Denoising and Multi-Task Learning

Abstract: Traffic flow prediction is one of the fundamental components in Intelligent Transportation Systems (ITS). Many traffic flow prediction models have been developed, but with limitation of noise sensitivity, which will result in poor generalization. Fused Lasso, also known as total variation denoising, penalizes L1-norm on the model coefficients and pairwise differences between neighboring coefficients, has been widely used to analyze highly correlated features with a natural order, as is the case with traffic fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Polson et al [21] developed a traffic flows prediction model based on deep learning and found that the future traffic conditions are more similar to current ones as compared to those from previous days. Yang et al [22] proposed a Fused Ridge Multi-Task Learning (FR-MTL) model for forecasting traffic flow in multiple roads. Experimental results on actual traffic datasets confirm that the model has satisfying accuracy and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Polson et al [21] developed a traffic flows prediction model based on deep learning and found that the future traffic conditions are more similar to current ones as compared to those from previous days. Yang et al [22] proposed a Fused Ridge Multi-Task Learning (FR-MTL) model for forecasting traffic flow in multiple roads. Experimental results on actual traffic datasets confirm that the model has satisfying accuracy and effectiveness.…”
Section: Introductionmentioning
confidence: 99%